Дијагностичка вредност на анти-цикличните цитрулирани пептидни антитела кај пациенти со ревматоиден артритис - Љ. Дамјановска-Рајчевска; В. Анастасовска; Б. Зафировска; К. Гроздановски; Н. Марина; М. Грличков (Македонско лекарско друштво = Macedonian Medical Association, 2007)
The aim of the study was to determine the diagnostic value, specificity and sensitivity of anti-CCP antibodies (ACPA) as a new test for rheumatoid arthritis, in comparison with IgM RF. A cross-sectional study was carried out to analyze the prevalence of ACPA and IgM RF in the sera of 160 randomly selected patients from the Clinic of Rheumatology: 60 with RA, 50 with connective tissue diseases and other rheumatic diseases (non-RA) and 50 healthy controls (HC). All of the RA patients fulfilled the revised ACR classification criteria. Commercial anti-CCP ELISA kits and IgM RF Latex test were used. As expected, ACPA showed comparable sensitivity (66,8% vs. 68,3%) and higher specificity (98% vs. 87%) than IgM R, at optimal cut off values. The ROC curve was generated for both tests. AUC was greater for ACPA than for igM RF (0,92 vs 0,82). The presence of either ACPA or IgM RF increased the testing sensitivity to 76,6%. There was a positive significant correlation between ACPA and IgM RF, r=0,459, p<0,001. ACPA antibodies are very useful serological markers for the diagnosis of RA, with comparable sensitivity and higher specificity than IgM RF. For early and precise diagnosis of RA, the concomitant use of both tests is necessary .
Diagnostic value of anty-cyclic citrullinated peptide antibodies in patrients with rheumatoid arthritis